A integrina a2b1 na progressão tumoral mamária: papel no microambiente tumoral e na metástase - Moritz, Milene Nóbrega de Oliveira (2019)
The harmonic functioning of cells involves an orchestrated synchronization of signaling that maintains the balance between proliferation and cell death in healthy tissues. Eventually, gene mutations can occur and the accumulation of these alterations culminate in uncontrolled cellular divisions and consequently in the formation of malignant neoplasias. Breast cancer is the most frequent among women, with metastasis being the major cause of death. The triple negative subtype of breast cancer is one of the most aggressive tumors and there is no specific therapy for its treatment. Bone is the most common site for breast cancer metastasis and the existence of membrane receptors such as integrins on tumor cells assist in this addressing. In this study, divided into two chapters, we evaluated the role of α2β1 integrin in the metastasis of breast cancer. In the first chapter, we used alternagin-C, a protein that binds to α2β1 integrin and from the venom of Bothrops alternatus snake, and the transient silencing of the α2 subunit to verify the role of this receptor in mammary metastasis. The results demonstrated that alternagin-C decreased in 50% tumor cell adhesion to type I collagen and increased more than three times the expression of the metastasis suppressor 1 (MTSS1). In the second chapter, we used three in vivo models (Mammary Fat Pad-MFP, intracardiac-IC and intratibial-IT) of breast bone metastasis with human tumor cells in athymic nude mice. All three models were treated with the α2β1 integrin inhibitor, TCI-15, or superexpressing the α2 subunit in tumor cells that were injected into the animals with the aim of evaluate the role of α2β1 integrin specifically in breast tumor bone metastasis. With these models, we observed that α2β1 integrin plays a significant role in primary tumor growth (MFP model), but there were no significant results in later stages of bone metastasis (IC and IT models). In addition, we verified a biphasic expression of α2β1 integrin during the metastasis cascade, with lower expression in the metastatic cells compared to expression in the parental breast tumor cells. We also demonstrated that the metastatic cells express high levels of PTHrP (parathyroid hormone related protein), Gli2, and TGFβRII, which have been shown to contribute to bone destruction. These data suggest an inverse relation between α2 integrin expression and a bone destructive phenotype. Furthermore, TGF-β treatment decreased α2β1 integrin levels in metastatic cells, suggesting that TGF-β may influence the selection of tumor cells to bone through this integrin regulation. Taken together, these results demonstrated that α2β1 integrin is involved with different roles in metastasis cascade of breast cancer to bone. Thus, this study contributed to identify a possible molecular target for the treatment and prevention of triple negative breast cancer metastasis.